European Union's policymaking on sustainable waste management and circularity in agroecosystems: The potential for innovative interactions between science and decision-making - Duquennoi, Christian; Martinez, José (Frontiers in Sustainable Food Systems, 2022)
The European Economic Community (EEC) and later the European Union (EU) have issued policies on waste during the last 50 years. This paper aims at analyzing EEC and EU's policymaking on waste management and circularity in agroecosystems as compared with other sectors of waste management (e.g., municipal, industrial, construction waste, etc.). Even if founded on the same general principles, and especially the precautionary principle, policymaking on waste and by-product management in agroecosystems differs from waste management in other sectors. In particular, agricultural waste management has been excluded from the European Waste Framework Directive, from its start in 1975 to this day. The issue of waste and by-products in agroecosystems has been addressed in multiple Directives and Regulations, historically aiming at reducing the potential negative impacts of residual organic matter application in agriculture. In the last decade, the swiftly growing interest for circular economy has triggered a breakthrough in traditional waste management, potentially affecting all economic sectors and enforcing systemic perspectives rather than more conventional “silo” approaches. Circularity in agroecosystems should thus become a major subject of EU's policymaking, but may suffer from its lack of a general framework, contrary to waste in other sectors. Moreover, agricultural valorization of urban residual organic streams may face several roadblocks in between differing legislations for agroecosystems and for “non-agricultural” systems. A systemic approach of the question of residual matter in agroecosystems, backing a strong policymaking framework for the sector, would be necessary in this context. Science-policymaking interactions are necessary to tackle these issues and should take innovative forms to address their complexity. Policy briefs, Policy Labs and the new European Commission Scientific Advice Mechanism represent existing innovative tools to take the topic of policymaking for sustainable waste management and circularity in agroecosystems forward.